2009
DOI: 10.1007/s00223-009-9316-9
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Osteoporosis, Osteopenia, and Fractures Among Adults with Cystic Fibrosis: A Systematic Literature Review with Meta-Analysis

Abstract: Observational studies have indicated a high but heterogeneous prevalence of low bone mineral density for adult patients with cystic fibrosis. Fracture complications were also described. The objective of this study was to determine the prevalence of osteoporosis, osteopenia, and fractures among adult patients with cystic fibrosis. A systematic literature review was conducted using electronic databases. The keywords used were "cystic fibrosis [MeSH] AND bone density." Original studies were eligible if they repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(83 citation statements)
references
References 26 publications
1
72
0
10
Order By: Relevance
“…Several studies described lower bone mass density (BMD) in patients with CF, which increases fracture risk [5][6][7][8] . Bone fractures can cause pain, decrease respiratory status, and are a contraindication for lung transplantation in these patients 9,10 . Cross-sectional studies in adults (age range from 16-60 years) with CF demonstrated that 6 to 68% had Z-scores ≤-2.0 8,[11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies described lower bone mass density (BMD) in patients with CF, which increases fracture risk [5][6][7][8] . Bone fractures can cause pain, decrease respiratory status, and are a contraindication for lung transplantation in these patients 9,10 . Cross-sectional studies in adults (age range from 16-60 years) with CF demonstrated that 6 to 68% had Z-scores ≤-2.0 8,[11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Dane zebrane przez Paccou i wsp. [15] wskazują na występowanie osteo porozy u blisko 24% chorych na CF, osteopenii u 38%, zła mań kręgów doznało 14%, a innych złamań ok. 20% pac jentów.…”
Section: Schorzenia Współwystępująceunclassified
“…Pomimo upływu ponad 30 lat od pierwszych badań, temat ten nadal jest aktualny i poruszany przez wielu autorów, szczególnie w ostatnim dziesięcioleciu. Według danych zebranych przez Paccou i współautorów osteoporoza dotyka 23,5% chorych na mukowiscydozę, 38% chorych ma osteopenię, złamań kręgów doświadczyło 14% pacjentów natomiast innych złamań 19,7% [6]. Etiologia zmian gęstości kości w przebiegu mukowiscydozy jest wieloprzyczynowa: niedobór witamin głównie jako wynik niewydolności trzustki, cukrzyca, leczenie przewlekłego zapalenia oskrzeli za pomocą glikokortykosteroidów, niedobór hormonów płciowych oraz obecność niektórych cytokin.…”
Section: Występowanie Osteoporozy W Mukowiscydozieunclassified